Ordinary angels [videorecording (Blu-Ray + DVD)] - Tilly, Meg; Fremon, Kelly; Swank, Hilary; Ritchson, Alan, 1984-; Travis, Nancy, 1961-; Acker, Amy, 1976-; Jones, Tamala; Powell, Drew, 1976-; Sorel, Nancy, 1964-; Sy, Stephanie; Hughes, Skywalker; Mitchell, Emily (Actress) (Lionsgate, 2024)
Sharon is a firece but struggling hairdresser in small-town Kentucky who discovers a renewed sense of purpose when she meets Ed, a widower working hard to provide for his two daughters. While his youngest daughter waits for a liver transplant, Sharon sets her mind to helping the family and will move mountains to do it.